18 t - 18 t * 30% = 18 t - 17 * 0,3 = 18 t - 5,4 t = 12,6 t
Answer:
520
Step-by-step explanation:
= 650 - (97.50 + 97.50/3)
= 650 - 130
= 520
Answer:
zero of a polynomial can be defined as the points where the polynomial become 0 as a whole.
An equation formed with variables, exponents and coefficient together with operation and an equal sign is called polynomial equation.
I hope this will help you
Answer:
421.875
Step-by-step explanation:
because the formula of the rectangular prism is l*w*h
-2(x + 3) = -2(x + 1) - 4
-2x - 6 = -2x - 2 - 4
0x = -6 + 6
0x = 0
x = unknown